The Effect Of Demonstration And Breastfeeding Assistance On Breastfeeding Ability Postpartum Mother - Merlyna Suryaningsih; Qurrotu Aini (NHM PRESS, 2020)
Exclusive breastfeeding according is breastfeeding alone without the addition of other liquids such as formula milk, oranges, honey, tea water, water, and without solid food ingredients such as bananas, papaya, milk porridge, biscuits, rice porridge and the team. Breastfeeding is recommended fot a period of 6 months. Preliminary study Irna C Room Syarifah Ambami Rato Ebhu general hospital Bangkalan 10 postpartum consist of 7 respondents of mothers who have difficulty breastfeeding. The purpose of the research is to analyze the effect of demonstration and breastfeeding assistence on breastfeeding postpartum mother inIrna C Room Syarifah Ambami rato ebhu general hospital bangkalan. The research used a quasi-experimental method with independent were Demonstration and Breastfeeding Assistance and the dependent variable was the ability to breastfeeding in postpartum mothers. the population were 18 respondents. The sampling technique used simple random sampling. The research sample of 18 respondents with 9 respondents from the treatment group and 9 respondents from the control group. The research showed that in analysis of the control and treatment groups used an independent T-test obtained from the value of ρ: 0,000<α: 0.05. This means that H0 was rejected, so there was a difference in the ability of breastfeeding mothers between the treatment and control groups for postpartum mothers in Irna C Room Syarifah Ambami Rato Ebhu general hospital Bangkalan. It is hoped that this research can provide benefits and knowledge as a health education to increase mother's knowledge about proper breastfeeding techniques and motivate a mother to give exclusive breastfeeding to her baby.